The Influence of the Gamification-Based OIDECCA Model on Student Achievement Motivation in Science Subjects in Class Vll At SMPN 6 Siak Hulu - Wahyu Anggrayeni; Ibnu Hajar (Universitas Trunodjoyo Madura, 2025)
The purpose of this study is to determine how the gamification-based OIDECCA learning model has an impact on students' motivation to excel in Natural Sciences (IPA) subjects in grade VII at SMP Negeri 6 Siak Hulu, Kampar Regency, in the 2024/2025 academic year. The OIDECCA (Observe, Idea, Design, Create, Communication, Reflection, and Assessment) model is an innovative approach that combines gamification elements to create an interactive, engaging, and encouraging learning experience. The method used was a quasi-experiment with a design of an unequal control group. The sample consisted of 54 students who were selected through a simple random sampling technique. Data collection instruments are in the form of questionnaires, observations, interviews, and documentation. The results showed a significant increase in achievement motivation in the experimental class with an average final score of 82.34%, compared to the control class which obtained 81.46%. The most improved indicator in the experimental class was learning independence. These findings show that the application of the gamification-based OIDECCA model is able to increase students' motivation to achieve, and can be recommended as an innovative learning strategy in science learning.